The optimal design and 4E analysis of double pressure HRSG utilizing steam injection for Damavand power plant. (1st January 2017) - Mokhtari, Hamid; Ahmadisedigh, Hossein; Ameri, Mohammad
Abstract: Energy, Exergy, Exergoeconomic and Environmental (4E) analysis of combined cycle power plant utilizing the method of steam injection into the combustion chamber is performed in the current study. Steam is supplied from low pressure (LP) side of the heat recovery steam generator (HRSG). According to genetic algorithm's results, the steam injection elevates the total combined cycle power by 2 MW while lowers the design costs considerably at optimum state. Some parameters restrict the steam injection usage within combined cycles that could be noted as Gas turbine power decline; Gas turbine loss increase due to pressure loss; HRSG's manufacturing costs growth; opposition between high and low pressure flow rate variations; NOX and CO emission costs dependency on optimum conditions. This paper discusses the above limitations for implementation of such technology in combined cycles. At the optimum point, Exergy and thermal efficiencies values increased from 42% and 47.6% to 47.28% and 48.94% respectively. Optimum pinch and approach temperatures for HP and LP sides were computed to be 35, 20, 17 and 37.5, respectively. Also, the optimum value of X parameter is 23.28%; X is defined as the ratio of steam to the inlet air flow rate divided by the other fraction which is the ratio of fuel to input air flow rate while there is no steam injection into the combustion chamber. Highlights: 4E analysis of CCPP utilizing steam injection. HRSG design for steam injection condition. HRSG optimization for power loss compensation in CCPP in steam injection condition. Sensitivity analysis of combined cycle by steam injection flow rate. Investigation of the environmental effects of steam injection into the CC.